2021
DOI: 10.1021/jacs.0c10792
|View full text |Cite
|
Sign up to set email alerts
|

Photoactive G-Quadruplex Ligand Identifies Multiple G-Quadruplex-Related Proteins with Extensive Sequence Tolerance in the Cellular Environment

Abstract: G-Quadruplex (G4) is a noncanonical nucleic acid secondary structure with multiple biofunctions. Identifying G4-related proteins (G4RPs) is important for understanding the roles of G4 in biology. Current methods to identify G4RPs include discovery from specific biological processes or in vitro pull-down assays with specific G4 sequences. Here, we report an in vivo strategy used to identify G4RPs with extensive sequence tolerance based on G4 ligand-mediated cross-linking. Applying this method, we identified 114… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 38 publications
2
46
0
Order By: Relevance
“…In principle, the approach we describe here should be applicable to a wide range of cell types and cell states, which in turn may help reveal specific differences in G4 interactomes and biology. During the revision of this article, we became aware of an independent study that involved a pyrrolidine derivative of PDS 50 and reported the identification of G4-related proteins in human SV589 and MM231 cells 51 . Although we noted some overlap between the studies (61 shared protein candidates), which somewhat validates the independent approaches, most of the G4-associated proteins identified by our CMPP approach were not found in the independent study.…”
Section: Discussionmentioning
confidence: 99%
“…In principle, the approach we describe here should be applicable to a wide range of cell types and cell states, which in turn may help reveal specific differences in G4 interactomes and biology. During the revision of this article, we became aware of an independent study that involved a pyrrolidine derivative of PDS 50 and reported the identification of G4-related proteins in human SV589 and MM231 cells 51 . Although we noted some overlap between the studies (61 shared protein candidates), which somewhat validates the independent approaches, most of the G4-associated proteins identified by our CMPP approach were not found in the independent study.…”
Section: Discussionmentioning
confidence: 99%
“…SERBP1 structure and its RNA recognition and binding activity are poorly characterized. SERBP1 was reported to bind preferentially to GC-rich motifs (Kosti et al, 2020), subsequent studies revealed that these motifs could include G-quadruplexes (Su et al, 2021). SERBP1 was identified in the structures of nontranslating 80 S ribosomes, blocking the mRNA entrance channel suggesting that it serves to regulate mRNA translation (Ahn et al, 2015;Brown et al, 2018;Muto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…An approach to probe protein-G4 interactions is through the use of G4 ligands, and this was recently used to identify G4-binding proteins in cells. 57,58 A common G4 ligand used for such studies is pyridostatin (PDS; Figure 8A), which shows high selectivity for G4 folds over other DNA or RNA structures. 59 The same approach outlined herein was followed to study the impact of the PDS ligand added at 5 μ M for 30 min before following APE1 cleavage activity or binding as described above in buffered solutions with 50 mM K + ions and 10 mM Mg 2+ ions.…”
Section: Impact Of Ape1 Binding To the Vegf G4s In The Presence Of A G4 Ligandmentioning
confidence: 99%
“…These data demonstrate that G4 ligands block APE1 binding to parallel-stranded G4s; additionally, this may explain why, in the intracellular studies to identify G4-binding proteins, APE1 was not found in one study and not a major G4 binding partner in the second study. 57,58 The Sugimoto laboratory has reported the properties of DNA and its interactions with proteins can change with the addition of the cosolvent polyethylene glycol 200 (PEG-200) to the buffer; they propose PEG-200 functions to mimic the molecular crowding that occurs as a result of the high concentration of proteins in the cellular milieu, or that could also occur via water exclusion. 60,61 Studies were conducted following their guidelines with 20% PEG-200 added to the 50 mM Mg 2+ -containing buffer, and activity and binding assays were conducted.…”
Section: Impact Of Ape1 Binding To the Vegf G4s In The Presence Of A G4 Ligandmentioning
confidence: 99%